Suppression of co-channel interference in NGSO constellation system with interference alignment - Bing DU; Jiawang LI; Xianmei WANG; Wei LI; Xiangnan LIU; Haijun ZHANG (Tongxin xuebao)
Aiming at the problem that in the current space， non-geostationary satellite orbit （NGSO） constellation systems were increasing day by day， there are more and more satellite networks nearby orbiting using the same frequency band， and the problem of co-channel interference between NGSO constellation systems and between NGSO constellation systems and traditional geostationary satellite orbit （GSO） constellation systems had become increasingly serious， the interference alignment algorithms of wireless communication was proposed， which matches the precoding matrix of the characteristic channel at the transmitter according to the transmission channel information of the satellite network to alleviate the co-channel interference problem of the low-orbit satellite network.The ChinaSat， OneWeb and Fortran systems were used to simulate and compare the interference values before and after using the interference alignment algorithms， which proves the feasibility of the proposed method and provides a reference for future research on such problems.